Oceanographic parameters for the sample stations of Ludwig Prandtl cruise LP20160725 - Tristan Zimmermann; Andrea Pieper; Johanna Irrgeher; Daniel Pröfrock (PANGAEA, 2022)
Offshore wind energy is a steadily growing sector contributing to the worldwide energy production. The impact of these offshore constructions on the marine environment, however, remains unclear in many aspects. In fact, little is known about potential emissions from corrosion protection systems such as organic coatings or galvanic anodes composed of Al and Zn alloys, used to protect offshore structures. In order to assess potential chemical emissions from offshore wind farms and their impact on the marine environment water and sediment samples were taken in the surroundings of offshore wind farms of the German Bight between 25.07.2016 and 02.08.2016. At every sampling station oceanographic parameters were measured directly on board with respective probes of a multimeter covering pH, dissolved oxygen, temperature and conductivity.
In: Zimmermann, T et al. (2022): Seawater and sediment data from surroundings of offshore wind farms in the German Bight collected during Ludwig Prandtl cruise LP20160725 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.943765